1999
DOI: 10.1111/j.1151-2916.1999.tb02224.x
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of Barium Osumilite Glass

Abstract: The crystallization of stoichiometric barium osumilite (BaMg 2 Al 6 Si 9 O 30 ) glass manufactured by melting or by sol-gel processing using an all-alkoxide route (AAR) or a partial-alkoxide route (PAR) using mixed alkoxides and salts has been characterized by thermal methods, phase analysis, and microstructural analysis. In all glasses, crystallization with heat treatment at a finite heating rate (1 or 10 K/min) occurs via an initial phase separation, leading to regions devoid of and enriched in BaO. In PAR g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 20 publications
(32 reference statements)
0
14
0
Order By: Relevance
“…4b), which has been previously reported during the devitrification of BaO-containing M 2 A 2 S 11 glasses 4 and BMAS glasses. 2 These previous studies suggested that the (0 0 1) and (4 2 0) planes of cordierite were parallel to the respective planes of osumilite, and that the epitaxial nucleation of cordierite on osumilite was caused by their similar lattice parameters: a is 9.770Å in ␣-cordierite and 10.160Å in Baosumilite.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…4b), which has been previously reported during the devitrification of BaO-containing M 2 A 2 S 11 glasses 4 and BMAS glasses. 2 These previous studies suggested that the (0 0 1) and (4 2 0) planes of cordierite were parallel to the respective planes of osumilite, and that the epitaxial nucleation of cordierite on osumilite was caused by their similar lattice parameters: a is 9.770Å in ␣-cordierite and 10.160Å in Baosumilite.…”
Section: Resultsmentioning
confidence: 95%
“…M 2 A 2 S 7 crystal → M 2 A 2 S 5 crystal + 2 mol of vitreous SiO 2 (2) As mentioned in the beginning of Section 3, the BMAS glass devitrification behaviour is determined by the local glass composition. Therefore, when the glass was locally enriched in Mg, primary Mg-rich phases formed instead of the usual Ba- Fig.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Metallic glasses do not retain their atomic structure obtained on production and the rate of change is dependent on the conditions under which a sample is stored [2]. It has also been reported that the method of preparation of a silicate glass, by sol-gel or by conventional melting, affects its structure and therefore its crystallization behavior [3]. Moreover, it is suggested in many studies that the stability of metallic glasses is influenced by the production process and the composition, which lead to different initial structure and energy states [4].…”
Section: Introductionmentioning
confidence: 98%